A rare cause of chronic abdominal pain among children - A case report - Krisztina Csuzi; Orsolya Boda; Robert Neumann; Gergely Peter Toth (Open Journal of Pediatrics and Child Health - Peertechz Publications, 2021)
Trichobezoar is a concretion of chewing and swallowing hair or any other indigestible materials that accumulate in the gastrointestinal tract. Rapunzel syndrome refers to a rare condition when a gastric trichobezoar extends into the small bowel. We describe the case of a 16-year-old female who presented with chronic abdominal pain, loss of appetite and weight loss. Based on her past medical history, trichophagia has already been revealed at preschool age. Imaging tests indicated a large filling of the stomach. Upper gastrointestinal endoscopy showed a large trichobezoar in the stomach with prolongation through the pylorus. The patient underwent exploratory laparotomy and the trichobezoar was removed. Upper gastrointestinal endoscopy is the preferred modality for diagnosis and in most cases the treatment is surgical.